Diagnosis of the new genus Agnathia (Pycnogonida, Callipallenidae) and description of two new species from southern Australia - Staples, D.a. (Zootaxa, 2021)
A new genus of Callipallenidae, Agnathia, is established to accommodate two new species of pycnogonid from southern Australia; A. aria and A. chuki. Both new species are represented by adult and sub-adult forms. Gravid females and ovigerous and larvigerous males are represented. Postembryonic growth stages are recorded and briefly discussed. The presence of six-segmented ovigers in males of one species, as opposed to the usual ten segments in both sexes, is recorded. Genera that share morphological relationships are discussed and a key to these genera is provided. The genera Bradypallene, Pycnopallene and Safropallene are reassessed and reassigned to family incertae sedis.